The resting‐state neurovascular coupling relationship: rapid changes in spontaneous neural activity in the somatosensory cortex are associated with haemodynamic fluctuations that resemble stimulus‐evoked haemodynamics. Issue 6 (10th July 2013) - Bruyns‐Haylett, Michael; Harris, Sam; Boorman, Luke; Zheng, Ying; Berwick, Jason; Jones, Myles
Abstract Although promise exists for patterns of resting‐state blood oxygen level‐dependent (BOLD) functional magnetic resonance imaging (fMRI) brain connectivity to be used as biomarkers of early brain pathology, a full understanding of the nature of the relationship between neural activity and spontaneous fMRI BOLD fluctuations is required before such data can be correctly interpreted. To investigate this issue, we combined electrophysiological recordings of rapid changes in multi‐laminar local field potentials from the somatosensory cortex of anaesthetized rats with concurrent two‐dimensional optical imaging spectroscopy measurements of resting‐state haemodynamics that underlie fluctuations in the BOLD fMRI signal. After neural 'events' were identified, their time points served to indicate the start of an epoch in the accompanying haemodynamic fluctuations. Multiple epochs for both neural 'events' and the accompanying haemodynamic fluctuations were averaged. We found that the averaged epochs of resting‐state haemodynamic fluctuations taken after neural 'events' closely resembled the temporal profile of stimulus‐evoked cortical haemodynamics. Furthermore, we were able to demonstrate that averaged epochs of resting‐state haemodynamic fluctuations resembling the temporal profile of stimulus‐evoked haemodynamics could also be found after peaks in neural activity filtered into specific electroencephalographic frequency bands (theta, alpha, beta, and gamma). This technique allows investigation of resting‐state neurovascular coupling using methodologies that are directly comparable to that developed for investigating stimulus‐evoked neurovascular responses.